2001
DOI: 10.1177/00027640121958249
|View full text |Cite
|
Sign up to set email alerts
|

Running in the Shadows in Campaign 2000

Abstract: Editorial cartoons contribute to candidate image development by offering condensed and simplified metaphoric portrayals. This study identifies the rhetorical fantasia advanced by cartoonists in their metaphors about Al Gore and George Bush through five themes of leadership during the early months of Campaign 2000: character, competence, viability, independence, and charisma. The cartoons reflected overall campaign strategies by attaching character issues to Gore and competence issues to Bush. However, the camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Within the frame, an editorial cartoon usually comprises two distinct levels: one is imaginary stories about a make-believe world, while the other, the referent, refers to real-life events and characters. This dichotomy has been referred to as a process of fantasia (Edwards, 2001). The frame’s compositional power lies in its simplicity but possesses enough complexity to be applicable to a wide variety of subjects while subtle enough to withstand and accommodate frequent visual distortions and alterations.…”
Section: Research Literature: Accounting Stereotypes Humour and Newsmentioning
confidence: 99%
“…Within the frame, an editorial cartoon usually comprises two distinct levels: one is imaginary stories about a make-believe world, while the other, the referent, refers to real-life events and characters. This dichotomy has been referred to as a process of fantasia (Edwards, 2001). The frame’s compositional power lies in its simplicity but possesses enough complexity to be applicable to a wide variety of subjects while subtle enough to withstand and accommodate frequent visual distortions and alterations.…”
Section: Research Literature: Accounting Stereotypes Humour and Newsmentioning
confidence: 99%
“…It has been observed that five leadership themes including character, competence, viability, independence, and charisma were mostly depicted in the political cartoons for image building of presidential candidates. It has also been found in such studies that during campaign cartoonists highlight candidates' political activities while during their presidential tenure the cartoonists focus on policy matters (Conner, 2005;Edwards, 2001, Palmer, 2011.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is concluded that humour in metaphor-based nominal compounds is produced by recognition and appropriate resolution of the incongruity between the source and the target domains of metaphor on the one hand, and the literal and the figurative meanings of the compound on the other (Kang 2016: 376). Apart from verbal metaphor, visual metaphor is attested to be one of the most common humour mechanisms in cartoon drawing (Templin 1999: 21;Edwards 2001Edwards : 2142El Refaie 2003;Plumb 2004;Tsakona 2009). The elements come from different domains and there is a likelihood that they may be incongruous to one another and thus result in the creation of humorous effect (Tsakona 2009(Tsakona : 1180.…”
Section: Literature Review 21 CL Endeavours In Humour Researchmentioning
confidence: 99%